Strengths and Weaknesses in Securities Market Regulation : A Global Analysis - Elliott, Jennifer (IMF Working Papers; Working Paper, 2007)
This paper examines the strengths and weaknesses of securities regulatory systems worldwide with a view to a better understanding of common problems and areas of global concern. We found that a consistent theme emerges regarding the lack of ability of regulators to effectively enforce compliance with existing rules and regulation. In many countries, a combination of factors, including insufficient legal authority, a lack of resources, political will and skills, has undermined the regulator's capacity to effectively execute regulation. This weakness is more acute in areas of increased technical complexity such as standards for and supervision of the valuation of assets and risk management practices.